Geopolitics and its implications for tax administration - Al-Ttaffi, Lutfi Hassen Ali (2016)
Geopolitical differences are often evident, where continuous political conflicts and instability exist, both within and among nations.Middle East is a fertile region for the existence of such conflicts, and thus the geopolitical differences exist, in some countries.However, the geopolitical differences issue is not confined to the matter itself, but the environment and mistreatment by the regimes create additional issues and challenges.According to the social influence theory, the behaviour of people is intentionally or unintentionally influenced by their surrounding environment.Therefore, the different geopolitics of people results in different attitude, and likely leads to the different behaviours among individuals.The geopolitical circumstances pose issues and challenges to government in administrating law and policy, including in the area of taxation.The government, particularly the tax administrators, need to understand the geopolitical differences in administering the tax laws and accordingly come up with a strategy that will ensure efficient collection of tax.This paper provided a brief concept of geopolitical differences and accordingly discussed key issues and challenges that are faced by the tax authority.